The Effect of Knowledge Orchestration On Dynamic Capabilities: An Analytical Research in the Iraqi Media Network - Yousuf Salman , Riyadh; Jasim Mohammed, Nisreen (Journal of Economics and Administrative Sciences, 2024)
This research aims to know the effect of the knowledge orchestra with its dimensions (knowledge mobilization, knowledge acquisition, knowledge coordination, knowledge sharing, and knowledge integration) on the dynamic capabilities with its dimensions (environmental sensing capabilities, opportunity investment capabilities, resource rearrangement capabilities, marketing capabilities, and technological capabilities). The main problem of this research was represented by the current question (Was the Iraqi Media Network able to invest the knowledge orchestra in achieving distinguished performance across having dynamic capabilities?). The Iraqi Media Network took a field of application for these variables, as the research sample included the senior leaders of the Iraqi Media Network, their numbers were 134 being between a director of a directorate, an assistant director, and a head of a department. The research used the quantitative method and the questionnaire was the main tool for collecting data and information, and the research used the SPSS program (v. 25) for data analysis. The results of the study concluded that there is a significant and positive influence and correlation between each dimension of the orchestra's knowledge operations and its dynamic capabilities. Also, results of the research reported that the Media Network showed its modules to mobilize knowledge through adopting communication patterns that are harmonious with its orientation towards having intellectual capital that distinguishes it from others, particularly it works to expand the knowledge base, such as diversity in knowledge fields within its current and future staff.